2022
DOI: 10.1186/s12943-022-01679-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/STAT3 signaling in tumor cells restricts the expression of frameshift-derived neoantigens by SMG1 induction

Abstract: Background The quality and quantity of tumor neoantigens derived from tumor mutations determines the fate of the immune response in cancer. Frameshift mutations elicit better tumor neoantigens, especially when they are not targeted by nonsense-mediated mRNA decay (NMD). For tumor progression, malignant cells need to counteract the immune response including the silencing of immunodominant neoantigens (antigen immunoediting) and promoting an immunosuppressive tumor microenvironment. Although NMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…It has been reported that cancers with a high frequency of NMD-insensitive frameshift mutations show increased immune infiltration and are associated with a better outcome after treatment with immune checkpoint inhibitors (27,28). Consistent with this, NMD inhibition results in strong immune responses and reduced tumor growth in vivo (22)(23)(24)(25). Our findings that NMD inhibition results in decreased tumorigenicity in the HT1080 fibrosarcoma model is fully in line with these reports.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It has been reported that cancers with a high frequency of NMD-insensitive frameshift mutations show increased immune infiltration and are associated with a better outcome after treatment with immune checkpoint inhibitors (27,28). Consistent with this, NMD inhibition results in strong immune responses and reduced tumor growth in vivo (22)(23)(24)(25). Our findings that NMD inhibition results in decreased tumorigenicity in the HT1080 fibrosarcoma model is fully in line with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, our results provide insights into the molecular mechanisms by which NMD activity benefits tumorigenicity of a classical cancer model system. Together with recent reports providing evidence for NMD's beneficial role in the development of a variety of different cancer types (22)(23)(24)(25), our findings suggest that in many cases, inhibition of NMD might represent a promising strategy to reduce tumor growth and prevent metastasis.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations